1991
DOI: 10.1515/cclm.1991.29.12.805
|View full text |Cite
|
Sign up to set email alerts
|

The Prognostic Value of Extracellular Matrix Component Concentrations in Serum During Treatment of Adult Respiratory Distress Syndrome with Extracorporeal CO2 Removal

Abstract: Summary:The time-dependent concentrations of hyaluronan, aminoterminal propeptide of type III procollagen, and laminin were determined in sera of 16 patients with severe adult respiratory distress syndrome during treatment with an extracorporeal CO 2 removal device. Patients were classified according to lung Parameters äs responders (n = 10) and non-responders (n = 6) to extracorporeal CO 2 removal. At the beginning of treatment strongly elevated serum concentrations of all studied extracellular matrix compone… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
13
0

Year Published

1994
1994
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(13 citation statements)
references
References 28 publications
0
13
0
Order By: Relevance
“…A high BAL HA level in ARDS was also found by Modig and Hallgren (30). In patients with ARDS treated with an extracorporeal CO 2 removal device, Kropf and colleagues (31) found that there was a sustained increase of serum HA level in those who did not respond to therapy. However, the molecular weight of HA was not measured in these experiments, and the exact role of different-sized HA remains unknown.…”
Section: Discussionmentioning
confidence: 99%
“…A high BAL HA level in ARDS was also found by Modig and Hallgren (30). In patients with ARDS treated with an extracorporeal CO 2 removal device, Kropf and colleagues (31) found that there was a sustained increase of serum HA level in those who did not respond to therapy. However, the molecular weight of HA was not measured in these experiments, and the exact role of different-sized HA remains unknown.…”
Section: Discussionmentioning
confidence: 99%
“…In nonsurvivors, the collagen content of the lung is increased two-to threefold after 2 weeks of ARDS and parallels the development of fibrosis [7]. Patients with ARDS dying after 7 days of respiratory failure have, in contrast to survivors, persistent elevation of extracellular matrix components (procollagen III) in the BAL and serum, indicating ongoing fibrogenesis [77,[128][129][130]. Patients with a procollagen III level greater than 1.75 U·mL -1 in BAL on day 7 had a 72% mortality rate compared with a 20% mortality rate in patients with a procollagen III level less than 1.75 U·mL -1 [131].…”
Section: Fibroproliferationmentioning
confidence: 99%
“…Elevations of extracellular matrix proteins such as procollagen type I, procollagen type III, hyaluronan, and laminin have been reported in the bronchoalveolar lavage and pulmonary edema fluid of patients with ALI implicating damage to the extracellular matrix (4,15,18).…”
mentioning
confidence: 99%